2017
DOI: 10.1136/bjophthalmol-2017-310346
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal fixational eye movements in strabismus

Abstract: Fixational instability could be a useful tool for mass screenings of children to diagnose strabismus in the absence of amblyopia and latent nystagmus. The increased disconjugacy of fixational eye movements and visually guided saccades in patients with strabismus reflects the disruption of the fine-tuning of the motor and visual systems responsible for achieving binocular fusion in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 35 publications
(6 reference statements)
8
55
0
Order By: Relevance
“…This disconjugacy was greater for patients with large-angle strabismus and impaired stereopsis (as a result of the misalignment of their eyes) than for patients with small-angle strabismus and preserved stereopsis (Figure 4 ). This study also found that drift was faster in patients with strabismus than in control subjects ( 46 ).…”
Section: Microsaccades In Ophthalmic Diseasesupporting
confidence: 53%
See 1 more Smart Citation
“…This disconjugacy was greater for patients with large-angle strabismus and impaired stereopsis (as a result of the misalignment of their eyes) than for patients with small-angle strabismus and preserved stereopsis (Figure 4 ). This study also found that drift was faster in patients with strabismus than in control subjects ( 46 ).…”
Section: Microsaccades In Ophthalmic Diseasesupporting
confidence: 53%
“…Black arrows indicate microsaccades, and gray arrows represent intersaccadic drift. From Ghasia et al ( 46 ).…”
Section: Microsaccades In Ophthalmic Diseasementioning
confidence: 99%
“…Blinks were identified and removed, as for the 200 milliseconds of data before and after them. Fixational saccades and quick phases of nystagmus were identified using an unsupervised clustering method [15,19,41]. The saccades amplitude is the absolute difference between eye positions at the start and end of a fixational saccade in patients without nystagmus or quick phase in patients with nystagmus.…”
Section: Eye Movement Recording and Analysismentioning
confidence: 99%
“…The increase in fixation instability is detrimental to vision as shown by reduced visual acuity and reading speeds when simulating eye position instability [9,10]. Patients with amblyopia have an increase in fixation instability [11][12][13][14][15][16][17]. This instability could arise from the presence of nystagmus or due to increased amplitude of involuntary saccades and inter saccadic drifts elicited during fixation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A high-resolution video-based eye tracker (EyeLink 1000) was used as described in our previous work. 31,32 The experiment protocols complied with the tenets of the Declaration of Helsinki and were approved by the Cleveland Clinic Institutional Review Board. Written informed consent was obtained from the parents or legal guardians on behalf of all the children.…”
Section: Eye Movement Recordingsmentioning
confidence: 99%